Role of non-adsorbing macromolecules in cell-cell interaction and cell-substrate adhesion - Deng, Xiaopeng (2015)
The realization that the depletion interaction plays an important role in cell-cell interaction and cell-substrate interaction has become manifest only within recent decades. This study aims to widen the applicability of the depletion hypothesis in cell-polymer system, since the depletion interaction is generic. In part of this study, the depletion interaction in bacterial phase separation as well as bacteria adhesion to surfaces is examined. Furthermore, the increased adhesion of tumor cells to plasma protein-coated surface has been obtained as well. These results agree with the concept of polymer depletion hypothesis and serve as evidence that depletion interaction also play a part in these cell-polymer systems.The impact of non-adsorbing macromolecules on red blood cell in diabetes mellitus has been detected as well. These data revealed important information of abnormal adhesion in vascular diseases. Our findings provide good support to the feasibility of the depletion hypothesis and may help in developing the application of depletion interaction, such as new therapeutic agents to vascular disorders.